Airport - Barton, Byron (New York, NY : Scholastic Inc., 1982)
Describes and pictures what happens from the time an airplane passenger arrives at an airport, and boards an airplane until the plane is in the air.
G2
Keywords: Airports -- Juvenile literature; Airports